PELAKSANAAN TUGAS ROOMBOY DI HOTEL GRAND BUNDA BUKITTINGGI SUMATERA BARAT - Tasya Siti Aulia; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Roomboy can be analogized as the spearhead of a hotel because of its role in cleaning room equipments for the sake of creating comfort in the hotel room. This research was conducted at the Grand Bunda Hotel which is a type of sharia hotel under the patronage of PT. Bunda Empat Pilar. This research aims to find out how Roomboy in cleaning Grand Bunda Bukittinggi hotel rooms in the Housekeeping Department with 2 (two) roomboys as the key informant. This research uses descriptive, qualitative methods, by which researchers describe the existing circumtances on the hotel to collect data and information, thereby using interview, observation, and documentation techniques. The results found in the research are that the implementation of roomboy services in cleaning hotel rooms can be categorized as good, but there are still some roomboys who are rather not attentive in cleaning the corners of hotel rooms. Keywords: Implementation, Roomboy, Cleaning